Sources of resistance to fusarium wil mocó cotton, Gossypium hirsutum marie-galante Hutch - Ponte, J. Júlio da; Sena-Silva, Mania do Socorro (Pesquisa Agropecuaria Brasileira, 2014)
In this paper four varieties of Mocó cotton, Gossypium hirsutum marie-galante Hutch., were tested in relation to parasitism by Fusarium oxysporum f. vasinfectum (Atk,) Snyder & Hansen, the cause Fusarium Wilt. The IAC-12 variety, Gossypium hirsutum hirsutum L., known for its high susceptibility, was included as a control. Two experiments were simultaneously conducted and characterized by two distinct inoculation methods: soil inoculation and dipping. The "São Miguel" variety of Mocó cotton showed high resistance. In fact, none of the plants was infected when the inoculum was applied exclusively in the soil. Only 50% of the "São Miguel" plants submitted to the dipping method were infected. This result was satisfactory considering the very severe treatment and the high inoculum concentration utilized. The other varieties of Mocó cotton ("Apa", "Cruzeta-Seridó" and "Cruzeta-Serra Talhada") showed moderate susceptibility to the pathogen.